Growth stimulation expressed gene 2 (ST2): Clinical research and application in the cardiovascular related diseases - Chen, Jinchao; Xiao, Peng; Song, Dan; Song, Dewei; Chen, Zhi; Li, Hongmei (Frontiers in Cardiovascular Medicine, 2022)
As an interleukin (IL)-1 receptor family member, scientists found that when circulating soluble growth stimulation expressed gene 2 (sST2) is low, its ligand, IL-33, will bind to ST2L to exert protective effects on various types of cells. On the other hand, competitive binding of IL-33 occurs when sST2 concentrations are increased, followed by a reduction in the amount available for cell protection. Based on this mechanism, the usage of sST2 is to identify the population of high-risk patients with cardiovascular disease. In recent years, the role of serum sST2 in the occurrence, diagnosis, prognosis, and treatment of cardiovascular diseases has been gradually accepted by doctors. This manuscript systemically reviews the biological functions and applications of sST2 in disease diagnosis and treatment, especially for cardiovascular diseases. In clinical testing, since IL-33 can negatively impact sST2 measurement accuracy, the properties of current assay kits have been summarized and discussed to provide a clear view of the clinical chemistry results. Although sST2 is a promising biomarker, there are few quantitative approaches available for clinical testing. In this context, a mass spectrometry (MS)-based approach might be an option, as this is a powerful analytical tool to distinguish structurally related molecules in the matrix and decrease false-positive results in clinical testing. Moreover, approaches developed based on MS would be an ideal way to further study sST2 standardization.